Police Discretion in Investigating Document Forgery and False Information Cases in Indonesia - Putra, Ichwan Fuad Chaerul; Markoni; Nardiman; Asri, Dyah Permata Budi (International Journal of Science and Society, 2025)
Discretion is a form of authority granted to law enforcement officers, including police investigators, to make decisions based on specific judgments to ensure the smooth progression of legal processes. The purpose of this study is to analyze the process of investigation, inquiry, and the determination of suspects in cases of document forgery. The theories utilized in this thesis research include the theory of investigation, the theory of law enforcement, and the theory of discretion. This research employs a normative juridical method, a legal research approach used to analyze and evaluate applicable legal norms and their application in practice. The findings indicate that in cases of document forgery, original evidence must be presented to investigators for subsequent seizure as valid evidence in proving the criminal act of document forgery. Photocopy evidence alone, unsupported by other evidence, is deemed inadmissible. In conclusion, the discretion applied in the investigation process and suspect determination is expected to align with legal principles. Excessive or improper use of discretion can lead to abuse of authority, ultimately undermining public trust in law enforcement institutions.